RE_BBC: Requirements Engineering in a Blockchain-Based Cloud: Its Role in Service-Level Agreement Specification - Singh, Irish; Lee, Seok Won (IEEE Software, 2020)
The cloud has several security and trust issues with the third-party provider. The blockchain-based cloud (BBC) system is an emerging technology that promises safe storage of big data on a cloud. The development of such a system needs requirements engineering (RE) in determining the requirements based on service-level agreements (SLAs). RE can provide a functional process to model and specify a SLA-based smart contract. The RE process for BBC ensures that the resulting SLA specifications are consistent, accurate, complete, verified, and validated. The RE process responds to the many challenges of the BBC and determines a novel direction to provide efficient and quality development of blockchainbased applications.
Keywords: Emerging technologies; Safe storage; Security and trusts; Service level agreement (SLAs); Service Level Agreements; Third parties